2016
DOI: 10.1016/j.ydbio.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

The mouse Foxi3 transcription factor is necessary for the development of posterior placodes

Abstract: The inner ear develops from the otic placode, one of the cranial placodes that arise from a region of ectoderm adjacent to the anterior neural plate called the pre-placodal domain. We have identified a Forkhead family transcription factor, Foxi3, that is expressed in the pre-placodal domain and down-regulated when the otic placode is induced. We now show that Foxi3 mutant mice do not form otic placodes as evidenced by expression changes in early molecular markers and the lack of thickened placodal ectoderm, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 97 publications
2
73
0
Order By: Relevance
“…Recently, otic expression of chick Dlx3 was shown to be epigenetically regulated by Kdm4b that is also expressed during otic placode specification . Similarly, loss of Foxi3 results in complete failure of otic placode induction in chick and mouse . Foxi1 and dlx3b interact with FGF signaling to regulate pax8 and pax2 expression during OEPD induction .…”
Section: Regionalization and Specification Of Individual Cranial Placmentioning
confidence: 99%
“…Recently, otic expression of chick Dlx3 was shown to be epigenetically regulated by Kdm4b that is also expressed during otic placode specification . Similarly, loss of Foxi3 results in complete failure of otic placode induction in chick and mouse . Foxi1 and dlx3b interact with FGF signaling to regulate pax8 and pax2 expression during OEPD induction .…”
Section: Regionalization and Specification Of Individual Cranial Placmentioning
confidence: 99%
“…Interestingly enough, several other transcription factors that are essential for vertebrate ear development, such as Eya1/Six1 (Xu et al, 1999; Zou et al, 2008), Gata3 (Duncan and Fritzsch, 2013; Karis et al, 2001) are also essential for both kidney and ear development. In addition, several other transcription factors are needed for ear development (Foxi3, Fgf3/10, Fgfr2, Sox9, Tfap2a (Alsina and Streit, 2016; Birol et al, 2016; Khatri et al, 2014; McMahon, 2016; Papadopoulos et al, 2016; Singh and Groves, 2016). Based on the evolution of statocysts in diploblasts, one could argue that evolution of the proneural gene regulatory network (GRN), involving possibly Eya1/Six1, Foxi3, Pax2/8 and Gata3 network of interacting factors and its dependence on Fgfr2 signaling (Pauley et al, 2003; Pirvola et al, 2000), evolved in ectodermal sensory placodes and was co-opted for mesodermal kidney development in triploblasts.…”
Section: Introductionmentioning
confidence: 99%
“…How all of these early transcription factors interact to define the level and topology of bHLH gene activation and how Wnt signaling fits in to regulate the size of the otic placode (Ohyama et al, 2007) remains to be determined experimentally. Loss of several factors can result in either incomplete invagination of the otic placode in mice mutant for Gata3 (Karis et al, 2001) or Pax2/8 (Bouchard et al, 2010), complete suppression of ear placode invagination such as in Foxi3 mutants (Birol et al, 2016; Singh and Groves, 2016) or in frogs exposed to RA (Fritzsch et al, 1998) or even incomplete formation of the ear following loss of Fgfr2 (Pirvola et al, 2000), indicating that several interactions are needed to move an otic placode forward to form an otocyst.…”
Section: Introductionmentioning
confidence: 99%
“…Pax2 / Pax8 are generally considered as molecular markers that define the domain. Interestingly, a recent study demonstrated that the most posterior Xth placode arises from a region of the ectoderm outside the area genetically marked by the Pax2‐Cre transgene (Birol et al, ). The observation that mSix1‐21‐NLSCre labeled some cells in the Xth placode/ganglion as described above, indicates that elements contained in the transgene is insufficient to drive Cre expression in the entire OEPD.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive cell movements are noted to accompany otic and epibranchial placode formation in chick (Streit, ), and such movements during otic and epibranchial development may be a common characteristics in chick and mouse. The other epibranchial placodes and the otic placode are dependent on the function of Foxi2/Foxi3 (Birol et al, ). The Xth placode is also unique in that its formation is independent of Foxi2/3 , and, therefore, its formation deserves further investigation.…”
Section: Discussionmentioning
confidence: 99%